Contemporary Sino-Indonesian relations - Tian, Tiecheng; Zarina Othman,; Aizat Khairi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sino-Indonesian relations are characterised by a complex interplay of economic opportunities and geopolitical challenges, shaping both nations' roles in Southeast Asia. This study examines Indonesia’s engagement with China, particularly through its participation in the Belt and Road Initiative (BRI) and the Jakarta-Bandung High-Speed Rail project, as a strategy to address critical infrastructure deficits. While Chinese investments have driven industrial modernisation, issues such as cost overruns, project delays, debt dependency, and environmental risks pose significant concerns. Geopolitically, Indonesia’s strategic location in the Indo-Pacific positions it as a pivotal player amidst intensifying regional rivalries. Despite its non-claimant status in the South China Sea dispute, Chinese incursions into Indonesia’s Exclusive Economic Zone (EEZ) near the Natuna Islands have prompted Jakarta to adopt a more assertive defence policy. Using a qualitative approach and secondary data analysis, this study explores how Indonesia balances economic cooperation with the geopolitical complexities arising from China’s growing influence and the United States’ counterbalancing strategies in the Indo Pacific. The findings reveal that while economic collaboration with China remains robust—particularly in trade, renewable energy, and electric vehicle manufacturing— Indonesia is increasingly diversifying partnerships and leveraging platforms like ASEAN and the Regional Comprehensive Economic Partnership (RCEP) to mitigate dependency risks. This study underscores the importance of pragmatic engagement, transparency, and trust-building to manage bilateral tensions while advancing mutual growth. Sino Indonesian relations profoundly influence Southeast Asia’s economic and geopolitical landscape, making sustainable and equitable practices essential for regional stability and shared development.